A proposal for structuring verbal idioms by semantic fields as a reference tool in teaching Spanish as a foreign language - Denisenko, Tatiana (Romanica Olomucensia, 2025)
This paper aims to analyse, on the one hand, how the theory of semantic fields can be applied to the teaching of idioms in the Spanish as a Foreign Language classroom (TSFL). On the other hand, an approach towards the organisation of Spanish idioms by semantic fields is suggested in order to create a consultation tool for both teachers and learners. Through the systematic tracking and extraction of idioms that express tastes, desires, and feelings, 27 semantic fields were identified for this purpose. Likewise, each semantic field was subdivided according to the syntagmatic combinatorics of the idioms. As a result, the compilation of each semantic field that was obtained facilitated the analysis of the paradigmatic relations of hyponymy-hyperonymy, synonymy, and antonymy that the idioms have between them. Taking into account the importance of understanding and proper usage of these phraseological units, it is essential to rely on real contextualised examples in the corpus of Spanish. All this suggests a new perspective on the teaching of phraseological units, although it is clear that we need to continue delving into the issue and investigate the semantic relations between idioms. Finally, the applicability of this consultation tool in the teaching of idioms in the TSFL classroom is evidenced, and the importance of continuing with improvements of this proposal is also underlined.
Keywords: idioms; semantic fields; paradigmatic relations; syntagmatic combinatorics; phraseodidactics; teaching SFL